Teofrasto. História das Plantas - Jorge Paiva (DIAITA, 2016)
This volume offers the first translation into Portuguese of the History of plants, by Theophrastus. The nature of the subject needed the collaboration of a Hellenist and a Botanist, in order to ensure the accuracy of the translation and the specificity of the footnotes and indexes. Beside the large number of footnotes, there is an introduction that identifies Theophrastus, his intellectual circle and the scientific structure of his exposition. The volume also includes a bibliography and seven indexes: two of Greek nomenclature and its translation into Portuguese, referring to the chapters of Theophrastus' text; four of Latin names given to the vegetal and animal species, referring to the footnotes; and a last one of toponyms.